2006
DOI: 10.1093/aler/ahl006
|View full text |Cite
|
Sign up to set email alerts
|

Capitalizing on Segregation, Pretending Neutrality: College Admissions and the Texas Top 10% Law

Abstract: In response to the judicial ban on the use of race-sensitive admissions, the 75 th Texas legislature passed H.B. 588, which guarantees admission to any Texas public college or university for all seniors graduating in the top decile of their class. We show that high levels of residential and school segregation facilitates minority enrollment at selective public institutions under the uniform admission law because black and Hispanic students who rank at the top of their class disproportionately hail from minorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 6 publications
0
52
0
Order By: Relevance
“…Since the inception of the TxTTPP, Texas's flagship institutions have experienced a limited reversal of minority enrollment declines attributed to the Hopwood decision (Chapa & Horn, 2007;Horn & Flores, 2003;Niu et al, 2006;Orfield & Miller, 1998;Tienda & Niu, 2006a). Yet the underrepresentation of minorities relative to the statewide proportions of minorities at the two flagship institutions of Texas remains a salient policy issue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the inception of the TxTTPP, Texas's flagship institutions have experienced a limited reversal of minority enrollment declines attributed to the Hopwood decision (Chapa & Horn, 2007;Horn & Flores, 2003;Niu et al, 2006;Orfield & Miller, 1998;Tienda & Niu, 2006a). Yet the underrepresentation of minorities relative to the statewide proportions of minorities at the two flagship institutions of Texas remains a salient policy issue.…”
Section: Resultsmentioning
confidence: 99%
“…The success of the TxTTPP has been debated in the literature. Despite the size of the Latina/o population in Texas and more than a decade of experience with the plan, studies have indicated that Latina/o students are still underrepresented at elite Texas colleges and universities (Chapa & Horn, 2007;Horn & Flores, 2003;Niu, Tienda, & Cortes, 2006;Tienda & Niu, 2006a. Even with the advantage afforded by the TxTTPP to minority students attending highly concentrated minority schools, students of color continue to have a lower likelihood than Whites of enrolling at the elite institutions of Texas (Niu et al, 2006).…”
Section: Txttppmentioning
confidence: 99%
“…The ethno-racial composition of high schools in the middle quartiles roughly approximates the Texas public high school student population except that African American students are slightly over-represented relative to their statewide share. Tienda and Niu (2006) show that minority students' chances of qualifying for the admission guarantee based on class rank are higher at schools where they constitute a larger share of the population, but their enrollment likelihood is lower owing to financial and information about college options .…”
Section: Methodsmentioning
confidence: 98%
“…Comparatively fewer studies consider whether and to what extent high school effects persist beyond the enrollment decision, and in particular whether race and ethnic variation in the quality of high school attended contributes to college performance; nevertheless, several studies suggest these influences exist (Summers and Wolfe, 1977;Massey, 2006;Schneider, et al, 2006;Niu, et al, 2006). For example, Massey (2006) shows that minority students who attend selective universities attend lower quality high schools that differ on a variety of difficult-to-measure dimensions, such as levels of violence and college-orientation, which in turn carry over to their college experiences.…”
Section: Introductionmentioning
confidence: 99%
“…By basing admissions decisions on high school class rank, percent plans provide a possible means for colleges to achieve racial diversity. In Texas, for example, the high degree of racial segregation across high schools contributes to a racially diverse pool of applicants in the top 10 % (Tienda and Niu 2006). 3 There have been several studies evaluating the effects of affirmative action bans (and alternative approaches for restoring minority enrollments) on minority students' collegegoing and completion (e.g., Card and Krueger 2005;Cortes 2010;Dickson 2006a;2006b;Howell 2010).…”
Section: A Brief Review Of Research On Racial/ethnic Preferences In Amentioning
confidence: 99%